2023
DOI: 10.1021/jacsau.2c00632
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Catalytic Behavior of Cobalt Oxides for CO2 Hydrogenation

Abstract: Cobalt oxide (CoO x ) catalysts are widely applied in CO2 hydrogenation but suffer from structural evolution during the reaction. This paper describes the complicated structure–performance relationship under reaction conditions. An iterative approach was employed to simulate the reduction process with the help of neural network potential-accelerated molecular dynamics. Based on the reduced models of catalysts, a combined theoretical and experimental study has discovered that CoO(111) provides active sites to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Consequently, it can be concluded that CoO plays an important role in H 2 adsorption and dissociation, thereby promoting CO 2 methanation. It is noteworthy that, Li et al 30 by calculating the energy profile of H 2 dissociation on different planes of CoO and Co 0 showed that H 2 dissociation on CoO (111) sites is comparable to Co 0 (111), indicating easy dissociation on CoO (111) similar to Co 0 , both characterized by low barriers. Considering the fact that, as mentioned earlier, the major crystallographic site of cubic CoO in the CoO-based thin-film catalyst is CoO (111), the higher CH 4 production on catalysts with higher CoO sites can be attributed to the feasible activation of H 2 on these CoO sites.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, it can be concluded that CoO plays an important role in H 2 adsorption and dissociation, thereby promoting CO 2 methanation. It is noteworthy that, Li et al 30 by calculating the energy profile of H 2 dissociation on different planes of CoO and Co 0 showed that H 2 dissociation on CoO (111) sites is comparable to Co 0 (111), indicating easy dissociation on CoO (111) similar to Co 0 , both characterized by low barriers. Considering the fact that, as mentioned earlier, the major crystallographic site of cubic CoO in the CoO-based thin-film catalyst is CoO (111), the higher CH 4 production on catalysts with higher CoO sites can be attributed to the feasible activation of H 2 on these CoO sites.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, introducing other elements into g-C 3 N 4 could build intermediary electronic states and/or elemental defects, boosting the separation of photogenerated charges and electron mobility, especially forming dual-active sites at interfaces . In particular, Co-based oxides (CoOx) have been demonstrated as promising materials for CO 2 hydrogenation due to their electronic and optical properties, which also help in intermediates’ stabilization after C–O cleavage by transferred surface electrons. For instance, Co 3 O 4 has been regarded as a favorable semiconductor material with remarkable CO 2 photoreduction to CH 4 and CO under simulated solar irradiation …”
Section: Introductionmentioning
confidence: 99%
“…In today’s era of global environmental degradation and energy crisis, CO 2 hydrogenation, as a mature technology for the utilization of CO 2 (greenhouse gas), enables the production of high-value-added products while consuming CO 2 , which is of considerable attraction. In the CO 2 hydrogenation reaction, water (H 2 O) is inevitably produced as a byproduct, when CO 2 and H 2 are converted to the target product. The presence of excess water in the system has been reported to lead to the deactivation of catalysts. Excess water molecules may compete with key reaction intermediates for the adsorption of active sites, resulting in the block or oxidation of active sites. , The accumulation of water may also accelerate the crystallization process and cause the sintering of catalysts .…”
Section: Introductionmentioning
confidence: 99%